The Efficacy of Maritime Logistics Connectivity in Reducing Regional Price Disparities of Essential Food Commodities across the Indonesian Archipelago - Sri Endang Kornita; Syarifah Akmal; Rahmah Hamidah (CV. HEI PUBLISHING INDONESIA, 2026)
The disparity in staple food prices across regions in Indonesia is a structural problem exacerbated by the country's geographical conditions as an archipelago. This study aims to examine the extent to which maritime logistics connectivity can reduce these price disparities. Using a mixed-methods approach, this study analyzed panel data from 34 provinces between 2020 and 2025 combined with semi-structured interviews involving 42 supply chain stakeholders. Estimation results indicate that a one-unit increase in port connectivity scores is associated with a 4.7%-6.2% decrease in the coefficient of variation of inter-island rice prices (p < 0.01). The Sea Toll Program has proven successful in narrowing the price gap between Java and Papua, from 47% in 2019 to 31% in 2025. This impact is further reinforced by the implementation of the National Logistics Ecosystem (NLE). The findings indicate that although maritime connectivity is an important prerequisite, intermodal logistics integration remains essential for achieving sustainable food price equity.